Anti-herpetic Activity of Macrocystis pyrifera and Durvillaea antarctica Algae Extracts Against HSV-1 and HSV-2 - Castillo, Estefanía; Duarte, Luisa F.; Corrales, Nicolas; Álvarez, Diana M.; Farías, Mónica A.; Henríquez, Adolfo; Smith, Patricio C.; Agurto-Muñoz, Cristian; González, Pablo A. (Frontiers in Microbiology, 2020)
Herpes simplex viruses (HSVs) type 1 (HSV-1) and type 2 (HSV-2) are highly prevalent in the human population, and the infections they produce are lifelong with frequent reactivations throughout life. Both viruses produce uncomfortable and sometimes painful lesions in the orofacial and genital areas, as well as herpetic gingivostomatitis, among other clinical manifestations. At present, the most common treatments against HSVs consist of nucleoside analogs that target the viral polymerase. However, such drugs are poorly effective for treating skin lesions, as they only reduce in 1-2 days the duration of the herpetic lesions. Additionally, viral isolates resistant to these drugs can emerge in immunosuppressed individuals, and second-line drugs for such variants are frequently accompanied by adverse effects requiring medical supervision. Thus, novel or improved therapeutic drugs for treating HSV lesions are needed. Here, we assessed the potential antiviral activity of aqueous extracts obtained from two brown macroalgae, Macrocystis pyrifera, and Durvillaea antarctica against HSVs. Both extracts showed antiviral activity against acyclovir-sensitive and -resistant HSV-1 and HSV-2. Our analyses show that there is significant antiviral activity associated with proteins in the extract, although other compounds also seem to contribute to inhibiting the viruses. Evaluation of the algae extracts as topical formulations in an animal model of HSV-1 skin infection significantly reduced the severity of the disease, more than acyclovir, as well as the duration of the herpetic lesions when compared to mock-treated animals with the Durvillaea antarctica extract performing best. Taken together, these findings suggest that these algae extracts may be potential phytotherapeutics against HSVs and may be useful for the treatment and reduction of common herpetic manifestations in humans.